Factors Affecting Students’ Attention in English Classrooms: A Qualitative Study at Junior High School - Nur Jannah; Darmayanti; Farisatma; Sari; Nur Rahmaniar Usman (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
Students’ attention is one of the factors that affects the overall learning process in the classroom. It facilitates the transfer of information into students’ conscious awareness and engages them in reasoning, which supports the development of their desired intellectual abilities. Previous studies have examined factors affecting students’ attention and teachers’ strategies to maintain classroom engagement; however, limited research has investigated students’ attention duration and the specific factors influencing attention in junior high school English classrooms, particularly in the context of Indonesian schools. Therefore, this study aimed to investigate the students’ attention and the factors affecting students’ attention during English learning in classes 8B and 9B at SMP IT Al Izzah Sorong, Papua. This study used a qualitative descriptive design. The participants consisted of 40 students from classes 8B and 9B. Data were collected through classroom observations and semi-structured interviews and were analyzed descriptively. The findings revealed that students’ attention was generally maintained only during the first ten minutes of the lesson, particularly during the opening stage. After this period, many students shifted their focus to other activities to avoid boredom and sleepiness. The study also identified several factors affecting students’ attention, including classroom noise, disruptive student behavior, fatigue, hunger, physical conditions, personal issues, and students’ interest and understanding of the lesson. Among these factors, classroom distractions, particularly noise and student behavior, emerged as the most dominant factors contributing to students’ lack of attention. These findings highlight the importance of creating a conducive learning environment and designing engaging instructional activities to sustain students’ attention throughout the learning process.